CHRISTIANITY, ART AND TRANSFORMATION - J.W. De Gruchy (Acta Theologica)
In this article, two papers, previously published in A Theological Odyssey. My Life in Writing (2014a), both based on Christianity, Art and Transformation (2001), are conflated. The first is a paper on “Christianity and Transformation” presented at a symposium on “Christianity and the Arts” at Andover – Newton Theological Seminary, Boston, 26 October, 1999. The second is a paper on “Art, Culture and Transformation” presented at the Conference on Arts and Reconciliation in Civil Society, University of Pretoria, 14-20 March 2005.